THU0097 The discrepancy between mrna and protein expression of the tumour-suppressor gene maspin in synovial tissue might contribute to synovial hyperplasia in rheumatoid arthritis (ra). (1st June 2001) - Schedel, J; Walder, E Jeisy; Simmen, B; Michel, BA; Gay, RE; Gay, S
Abstract : Background: RA is a chronic disease characterised by tumour-like features such as synovial hyperplasia, invasive growth of the synovium and joint destruction. Maspin is a member of the serpin family of protease inhibitors with gene sequence similarities to plasminogen activator inhibitor. Maspin exhibits also tumour-suppressor activity by inhibiting cell motility, invasion and metastasis, and is down-regulated in breast and prostate cancer. Objectives: We investigated the expression of maspin in RA synovial tissue and compared it with the expression in osteoarthritis (OA) and normal synovial tissues (NS). Methods: The expression of maspin was determined in synovial tissue samples obtained during synovectomy or arthroplastic surgery. Using specific primers for maspin, a 237 bp fragment was amplified from cDNA obtained from cultured RA (6), OA (4) and normal (1) synovial fibroblasts (SF) by reverse transcription polymerase chain reaction (RT-PCR). In addition, mRNA expression levels were determined quantitatively by real-time PCR (TaqMan). Using non-radioactive in situ hybridization, mRNA expression of maspin was investigated using snap-frozen and paraffin sections. To identify the cell types expressing maspin, immunohistochemistry was performed on serial tissue sections using monoclonal antibodies against CD3 (T cells) and CD68 (macrophages). SDS-PAGE and Western blotting was performed using anti-maspin antibodies to evaluate the protein expression in total synovial tissue and in cultured synovial fibroblasts (3rd -4th passage). Protein from normal breast tissue was used as positive control. Results: RT-PCR revealed expression of maspin in all cDNA samples from cultured synovial fibroblasts. By real-time PCR, maspin mRNA was found 2-fold decreased in RA-SF compared to OA-SF and 70-fold in comparison to NS-SF. Using in situ hybridization, maspin mRNA was expressed in RA as well as in OA and normal synovial tissue. Whereas in normal and OA samples, expression of maspin mRNA was restricted to synovial fibroblasts in the synovial lining and sublining, in RA, maspin could additionally be observed within perivascular infiltrates in mononuclear and multinucleated cells. Importantly, maspin transcripts were also found at sites of invasion into cartilage and bone. Interestingly, on the protein level, maspin could only be detected in normal breast tissue, but neither in RA synovial tissue nor in RA or OA synovial fibroblasts. Conclusion: Since maspin is not expressed in RA-SF on the protein level, it is hypothesised that the lack of maspin could contribute to the hyperplasia of the synovial tissue in RA.